ACCOUNTING CONSERVATISM: THE EFFECT OF FIRM PERFORMANCE, POSITIVE ACCOUNTING THEORY, AND LITIGATION RISK - Averio, Thomas (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study was to analyze the effect of firm performance, positive accounting theory proxied by bonus plan, debt covenant, and political cost, and litigation risk on accounting conservatism. The data used in this study is the annual report of food beverage subsector companies listed on Indonesia Stock Exchange in 2014-2019. The sampling technique being applied in this study is purposive sampling, with multiple linear regression. This results showed that firm performance and bonus plan have negative effect on accounting conservatism, while debt covenant, political cost, and litigation risk have no significant effect on accounting conservatism.Keywords: Accounting Conservatism, Firm Performance, Positive Accounting Theory, Litigation Risk.